2022
DOI: 10.1108/jeee-08-2021-0306
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant entrepreneurship with a focus on human and social capital as determinants of success: evidence from South Africa

Abstract: Purpose As a consequence of global changes, the landscape of immigration is changing. This brings opportunities for researching more nuanced aspects related to immigrant entrepreneurship in new contexts. The purpose of this paper is to establish the extent to which Africa-to-African immigrants leverage their social capital and human capital towards improving the success of their entrepreneurial ventures. Design/methodology/approach First-generation immigrant entrepreneurs within the Johannesburg area in Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
(173 reference statements)
0
5
0
Order By: Relevance
“…We are currently in the post-industrial, knowledge-based economy, and the factors of production have changed to intellectual capital, social capital and creative capital [17]. Social capital, as developed into networking, relationship formation and information accessibility, is an important success factor in career, business and personal development [10,11,18]. In the context of business, social capital forms the basis of business networks that is crucial for business development and personal growth [18,19].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…We are currently in the post-industrial, knowledge-based economy, and the factors of production have changed to intellectual capital, social capital and creative capital [17]. Social capital, as developed into networking, relationship formation and information accessibility, is an important success factor in career, business and personal development [10,11,18]. In the context of business, social capital forms the basis of business networks that is crucial for business development and personal growth [18,19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social capital, as developed into networking, relationship formation and information accessibility, is an important success factor in career, business and personal development [10,11,18]. In the context of business, social capital forms the basis of business networks that is crucial for business development and personal growth [18,19]. Among the benefits of business networks are shared knowledge, opportunities, connections, increased confidence and raised profile [9,20].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that personality quality with resilience as the core significantly improves entrepreneurial performance (Hmieleski and Carr, 2009). At the same time, entrepreneurship is a difficult process, which requires entrepreneurs to have comprehensive abilities (Cubero et al, 2022); among them, the excellent traits that entrepreneurs possess are crucial in the entrepreneurial process (Aldrich and Cliff, 2003), which helps to provide entrepreneurs with high motivation in the face of adversity and enhances the success rate of entrepreneurship (Urban et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Urban, Murimbika, and Mhangami's (2022) research explores how immigrant entrepreneurs in South Africa, influenced by global changes, utilize their social capital in developing nations to both positively and negatively affect their resource mobilization efforts and exploitation of entrepreneurial opportunities. The study reveals that structural and resource-related dimensions of social capital are crucial for achieving entrepreneurial success, indicating that more resources but lower costs facilitate entrepreneurial opportunity exploitation.…”
mentioning
confidence: 99%